On Certain Topological Structures of Summable Paranormed Sequence Space Defined in Two - Normed Space - Pahari, Narayan Prasad (Journal of Institute of Science and Technology, 2015)
Abstract on PDF Journal of Institute of Science and Technology, 2014, 19(2): 135-140